Cytokine levels predict 30-day mortality in octogenarians and nonagenarians with community-acquired pneumonia: a retrospective observational study - Héctor Pinargote-Celorio; Gemma Miralles; Miguel Cano; Esther Caparros; Joaquín Portilla; Gregorio González-Alcaide; José M. Ramos_Rincón (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

A comparison of genomic islands of differentiation across three young avian species pairs - Darren E. Irwin; Borja Milá; David P. L. Toews; Alan Brelsford; Haley L. Kenyon; Alison N. Porter; Christine Grossen; Kira E. Delmore; Miguel Alcaide; Jessica H. Irwin (Molecular Ecology, 2018)
Detailed evaluations of genomic variation between sister species often reveal distinct chromosomal regions of high relative differentiation (i.e., “islands of differentiation” in F ST ), but there is much debate regarding the causes of this pattern. We briefly review the prominent models of genomic islands of differentiation and compare patterns of genomic differentiation in three closely related pairs of New World warblers with the goal of evaluating support for the four models. Each pair (MacGillivray's/mourning warblers; Townsend's/black‐throated green warblers; and Audubon's/myrtle warblers) consists of forms that were likely separated in western and eastern North American refugia during cycles of Pleistocene glaciations and have now come into contact in western Canada, where each forms a narrow hybrid zone. We show strong differences between pairs in their patterns of genomic heterogeneity in F ST , suggesting differing selective forces and/or differing genomic responses to similar selective forces among the three pairs. Across most of the genome, levels of within‐group nucleotide diversity ( π Within ) are almost as large as levels of between‐group nucleotide distance ( π Between ) within each pair, suggesting recent common ancestry and/or gene flow. In two pairs, a pattern of the F ST peaks having low π Between suggests that selective sweeps spread between geographically differentiated groups, followed by local differentiation. This “sweep‐before‐differentiation” model is consistent with signatures of gene flow within the yellow‐rumped warbler species complex. These findings add to our growing understanding of speciation as a complex process that can involve phases of adaptive introgression among partially differentiated populations.

Ecology can inform genetics: Disassortative mating contributes to MHC polymorphism in Leach’s storm‐petrels ( Oceanodroma leucorhoa ) - Brian Hoover; Miguel Alcaide; Sarah Jennings; Simon Yung Wa Sin; Scott V. Edwards; Gabrielle A. Nevitt (Molecular Ecology, 2018)
Studies of MHC‐based mate choice in wild populations often test hypotheses on species exhibiting female choice and male–male competition, which reflects the general prevalence of females as the choosy sex in natural systems. Here, we examined mutual mate‐choice patterns in a small burrow‐nesting seabird, the Leach’s storm‐petrel ( Oceanodroma leucorhoa ), using the major histocompatibility complex (MHC). The life history and ecology of this species are extreme: both partners work together to fledge a single chick during the breeding season, a task that requires regularly travelling hundreds of kilometres to and from foraging grounds over a 6‐ to 8‐week provisioning period. Using a 5‐year data set unprecedented for this species ( n = 1078 adults and 925 chicks), we found a positive relationship between variation in the likelihood of female reproductive success and heterozygosity at Ocle‐ DAB 2, a MHC class IIB locus. Contrary to previous reports rejecting disassortative mating as a mechanism for maintaining genetic polymorphism in this species, here we show that males make significant disassortative mate‐choice decisions. Variability in female reproductive success suggests that the most common homozygous females (Ocle‐ DAB 2*01/Ocle‐ DAB 2*01) may be physiologically disadvantaged and, therefore, less preferred as lifelong partners for choosy males. The results from this study support the role of mate choice in maintaining high levels of MHC variability in a wild seabird species and highlight the need to incorporate a broader ecological framework and sufficient sample sizes into studies of MHC ‐based mating patterns in wild populations in general.

Recurrent selection explains parallel evolution of genomic regions of high relative but low absolute differentiation in a ring species - Darren E. Irwin; Miguel Alcaide; Kira E. Delmore; Jessica H. Irwin; Gregory L. Owens (Molecular Ecology, 2016)
Recent technological developments allow investigation of the repeatability of evolution at the genomic level. Such investigation is particularly powerful when applied to a ring species, in which spatial variation represents changes during the evolution of two species from one. We examined genomic variation among three subspecies of the greenish warbler ring species, using genotypes at 13 013 950 nucleotide sites along a new greenish warbler consensus genome assembly. Genomic regions of low within‐group variation are remarkably consistent between the three populations. These regions show high relative differentiation but low absolute differentiation between populations. Comparisons with outgroup species show the locations of these peaks of relative differentiation are not well explained by phylogenetically conserved variation in recombination rates or selection. These patterns are consistent with a model in which selection in an ancestral form has reduced variation at some parts of the genome, and those same regions experience recurrent selection that subsequently reduces variation within each subspecies. The degree of heterogeneity in nucleotide diversity is greater than explained by models of background selection, but is consistent with selective sweeps. Given the evidence that greenish warblers have had both population differentiation for a long period of time and periods of gene flow between those populations, we propose that some genomic regions underwent selective sweeps over a broad geographic area followed by within‐population selection‐induced reductions in variation. An important implication of this ‘sweep‐before‐differentiation’ model is that genomic regions of high relative differentiation may have moved among populations more recently than other genomic regions.

Male transmission ratio distortion supports MHC-linked cryptic female choice in the lesser kestrel (Aves: Falconidae) - Miguel Alcaide; Airam Rodríguez; Juan José Negro; David Serrano (Behavioral Ecology and Sociobiology, 2012)

On the relative roles of selection and genetic drift in shaping MHC variation - MIGUEL ALCAIDE (Molecular Ecology, 2010)
Genes of the major histocompatibility complex (MHC) have provided some of the clearest examples of how natural selection generates discordances between adaptive and neutral variation in natural populations. The type and intensity of selection as well as the strength of genetic drift are believed to be important in shaping the resulting pattern of MHC diversity. However, evaluating the relative contribution of multiple microevolutionary forces is challenging, and empirical studies have reported contrasting results. For instance, balancing selection has been invoked to explain high levels of MHC diversity and low population differentiation in comparison with other nuclear markers. Other studies have shown that genetic drift can sometimes overcome selection and then patterns of genetic variation at adaptive loci cannot be discerned from those occurring at neutral markers. Both empirical and simulated data also indicate that loss of genetic diversity at adaptive loci can occur faster than at neutral loci when selection and population bottlenecks act simultaneously. Diversifying selection, on the other hand, explains accelerated MHC divergence as the result of spatial variation in pathogen‐mediated selective regimes. Because of all these possible scenarios and outcomes, collecting information from as many study systems as possible, is crucial to enhance our understanding about the evolutionary forces driving MHC polymorphism. In this issue, Miller and co‐workers present an illuminating contribution by combining neutral markers (microsatellites) and adaptive MHC class I loci during the investigation of genetic differentiation across island populations of tuatara Sphenodon punctatus . Their study of geographical variation reveals a major role of genetic drift in shaping MHC variation, yet they also discuss some support for diversifying selection.

Captive breeding and reintroduction of the lesser kestrel Falco naumanni: a genetic analysis using microsatellites - Miguel Alcaide; Juan J. Negro; David Serrano; José L. Antolín; Sara Casado; Manel Pomarol (Conservation Genetics, 2010)

Erratum to: MHC class I genes of birds of prey: isolation, polymorphism and diversifying selection - Miguel Alcaide; Scott V. Edwards; Luis Cadahía; Juan J. Negro (Conservation Genetics, 2009)

MHC class I genes of birds of prey: isolation, polymorphism and diversifying selection - Miguel Alcaide; Scott V. Edwards; Luis Cadahía; Juan J. Negro (Conservation Genetics, 2009)

Extensive polymorphism and geographical variation at a positively selected MHC class II B gene of the lesser kestrel ( Falco naumanni ) - MIGUEL ALCAIDE; SCOTT V. EDWARDS; JUAN J. NEGRO; DAVID SERRANO; JOSÉ L. TELLA (Molecular Ecology, 2008)
Understanding the selective forces that shape genetic variation in natural populations remains a high priority in evolutionary biology. Genes at the major histocompatibility complex (MHC) have become excellent models for the investigation of adaptive variation and natural selection because of their crucial role in fighting off pathogens. Here we present one of the first data sets examining patterns of MHC variation in wild populations of a bird of prey, the lesser kestrel, Falco naumanni . We report extensive polymorphism at the second exon of a putatively functional MHC class II gene, Fana‐ DAB*1. Overall, 103 alleles were isolated from 121 individuals sampled from Spain to Kazakhstan. Bayesian inference of diversifying selection suggests that several amino acid sites may have experienced strong positive selection (ω = 4.02 per codon). The analysis also suggests a prominent role of recombination in generating and maintaining MHC diversity (ρ = 4 Nc = 0.389 per codon, θ = 0.017 per codon). Both the Fana ‐DAB*1 locus and a set of eight polymorphic microsatellite markers revealed an isolation‐by‐distance pattern across the Western Palaearctic ( r = 0.67; P = 0.01 and r = 0.50; P = 0.04, respectively). Nonetheless, geographical variation at the MHC contrasts with relatively uniform distributions in the frequencies of microsatellite alleles. In addition, we found lower fixation rates in the MHC than those predicted by genetic drift after controlling for neutral mitochondrial sequences. Our results therefore underscore the role of balancing selection as well as spatial variations in parasite‐mediated selection regimes in shaping MHC diversity when gene flow is limited.

Characterization, Polymorphism, and Evolution of MHC Class II B Genes in Birds of Prey - Miguel Alcaide; Scott V. Edwards; Juan J. Negro (Journal of Molecular Evolution, 2007)